Genomic loci associated with performance limiting equine overriding spinous processes (kissing spines). (5th December 2022) - Patterson Rosa, L.; Whitaker, B.; Allen, K.; Peters, D.; Buchanan, B.; McClure, S.; Honnas, C.; Buchanan, C.; Martin, K.; Lundquist, E.; Vierra, M.; Foster, G.; et al.
Abstract: Commonly known as "Kissing Spines" (KS), the pathological mechanisms underlying impingement and overriding of spinous processes (ORSPs) in horses are poorly understood. Thoroughbreds, Warmbloods, and stock-type breeds, including Paint Horses and Quarter Horses are at increased risk for developing clinical signs of KS. A total of 155 stock-type and Warmblood horses presented at collaborating veterinary clinics and hospitals were examined using a strict clinical and radiographical phenotyping scheme to grade each horse from 0 for unaffected controls to 4 for severe KS. Following genotyping with the Illumina Equine SNP70 array (Illumina, Inc.) a Genome Wide Association Study (GWAS) using 61, 229 filtered individual Single Nucleotide Polymorphisms (SNPs) was performed to the KS grade phenotype. Two significantly associated SNPs (BIEC2–668062 and BIEC2–668013) on chromosome 25 defined a ~1.4 Gb candidate region containing approximately 17 coding genes (EquCab3) and 195 ENSEMBL annotated variants. Investigation of the best associated SNP (BIEC2–668062) on chr25 demonstrates a significant correlation with an increase in one KS grade, on average, per A allele in this population. A significant effect of breed group, age, height or sex was not observed in this population. These preliminary results demonstrate the potential for KS diagnosis and preventative measures for WB/ST individuals supported by increased genetic risk for more severe KS grade. We propose further research including other affected breeds and evaluating causative variants, as well as the effect of BIEC2–668062 in these populations. Highlights: Phenotyping Kissing Spines (KS) using a strict clinical and radiographical scheme. Genome Wide Association to KS phenotype resulted in two significant chr25 polymorphisms. Best variant on chr25 correlates with an increase in one KS grade per A allele. Heritability estimates and preliminary findings suggest further genomic studies.